Stop prancing about: boys, dance and the reflective glance. Issue 5 (10th June 2014) - Edward, Mark
Abstract : Purpose: – The over-arching purpose of this paper is to provide a reflexive personal narrative of the inequalities experienced as the author grew up with a desire to dance; personal experiences which influenced the author to become an educator and eventually led the author to engage in some active research on the issue of boys and dance in secondary schools in the north of England. Design/methodology/approach: – This project is based on narrative interviews with young males, as the researchers seek to assess the current landscape of dance education within the UK. Interviews were conducted within two high school settings. Yet, this paper does not focus on the data produced in such interviews. Instead, it adopts a reflective methodology in terms of auto-critiquing the inquiry, exploring themes such as dancing negativity, homophobia and homonormativity. Findings: – The paper offers a brief critique of the literature around long-standing cultural ingrained discrimination experienced by boys who dance. Finally, and importantly, the paper offers a personal and intimate account reflecting on the author's experiences of engaging in research on male dancers in secondary schools. Originality/value: – This paper is a semi-autobiographical reflective inquiry which assesses the current issue of masculinities and dance, within adolescent educational settings. It is important in generating an awareness of the importance of individual and subjective reflective starting points for conducting research and the paper concludes how ethnographic research is never really neutral.